Painful Left Bundle Branch Block Syndrome Treated With Conduction System Pacing. A Report of Two Cases - Catalin Pestrea; Constantin Guzgan; Ecaterina Cicala; Radu Vatasescu (Clinical Case Reports)
ABSTRACT Painful left bundle branch block (LBBB) syndrome is a rare condition characterized by chest pain associated with the development of LBBB in the absence of myocardial ischemia. Although the mechanism of this entity is not fully understood, the occurrence of retrosternal chest pain is considered to be the consequence of ventricular dyssynchrony induced by LBBB. We present two cases of patients with non‐ischemic cardiomyopathy and chest pain associated with intermittent LBBB morphology. In the context of a reduced left ventricular ejection fraction, a wide QRS complex, and echocardiographic evidence of intraventricular dyssynchrony, successful conduction system pacing (CSP) (His bundle and left bundle branch area pacing, respectively) was performed to correct the LBBB completely. During the procedure, the diagnosis of painful LBBB syndrome was confirmed with clear, reproducible proof that the onset of chest pain was simultaneous with the occurrence of LBBB on the electrocardiogram, both spontaneously and during rapid atrial pacing, and remitted with spontaneous or with correction of the LBBB. The evolution of the patients was favorable, with the six‐month follow‐up showing complete remission of symptoms and recovery of LV function.